Same Work, Lower Grade? Student Ethnicity and Teachers' Subjective Assessments - Reyn van Ewijk (Tinbergen Institute, 2010)
Previous research shows that ethnic minority students perform poorer in school when they are taught by ethnic majority teachers. Why this is the case was unclear. This paper focuses on one important potential explanation: I examine whether ethnic majority teachers grade minority and majority students differently for the same work. Using an experiment, I rule out the existence of such a direct grading bias. I do find indirect evidence for alternative explanations: teachers report lower expectations and unfavorable attitudes that both likely affect their behavior towards minority students, potentially inducing them to perform below their ability level. Effects of having majority teachers on minority students' grades hence seem more likely to be indirect than direct.This discussion paper resulted in a publication in 'Economics of Education Review' (30) 1045-1058.
Keywords: I2; J15; 330; Ethnicity; Discrimination; Grading; Experiment; Studierende; Ethnische Diskriminierung; Hochschullehrer; Test; Niederlande